Inklusi Keuangan Syariah Bagi Penyandang Disabilitas dalam Perspektif Maqashid Syariah - Fatkur Huda Fatkur; Dikky Syadqomullah Syadqomullah; Anzal Atsmara Azis Azis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Financial inclusion is an important element in equitable economic development. However, people with disabilities still face obstacles in accessing Islamic financial services. In fact, the Islamic financial system based on the principles of al-'adl (justice) and maṣlaḥah (benefit) is in line with the goal of Maqāṣid al-Syarī'ah to protect property (hifz al-mal), soul (hifz al-nafs), and human dignity (ḥifẓ al-'irdh). This study aims to analyze the inclusion of Islamic finance for people with disabilities in Indonesia through a literature review (library research) with a qualitative descriptive approach to legal sources, scientific literature, and regulatory agency reports. The results of the study show that despite regulations such as Law No. 8 of 2016, the Compilation of Sharia Economic Law (KHES), and POJK No. 6/POJK.07/2022, the application of Maqāṣid al-Syarī'ah values in Islamic financial services has not been optimal due to the limitations of inclusive infrastructure, low literacy, and the absence of specific technical guidelines. This research emphasizes the need to integrate the principles of Maqāṣid al-Syarī'ah in digital policies, regulations, and innovations in order to realize an inclusive and socially just Islamic financial system.